Investigation of adequate closed form travelling wave solution to the space-time fractional non-linear evolution equations - Arefin, Mohammad Asif; Khatun, M. Ayesha; Uddin, M. Hafiz; İnç, Mustafa (Elsevier, 2022)
This work aims to construct exact solutions for the space-time fractional (2 + 1)- dimensional dispersive longwave (DLW) equation and approximate long water wave equation (ALW) utilizing the twovariable ( G' /G, 1/G)-expansion method and the modified Riemann-Liouville fractional derivative. The recommended equations play a significant role to describe the travel of the shallow water wave. The fractional complex transform is used to convert fractional differential equations into ordinary differential equations. Several wave solutions have been successfully achieved using the proposed approach and the symbolic computer Maple package. The Maple package program was used to set up and validate all of the computations in this investigation. By choosing particular values of the embedded parameters, we produce multiple periodic solutions, periodic wave solutions, single soliton solutions, kink wave solutions, and more forms of soliton solutions. The achieved solutions might be useful to comprehend nonlinear phenomena. It is worth noting that the implemented method for solving nonlinear fractional partial differential equations (NLFPDEs) is efficient, and simple to find further and new-fangled solutions in the arena of mathematical physics and coastal engineering. (c) 2021 Shanghai Jiaotong University. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)
Keywords: Riemann-Liouville fractional derivative; Space-time fractional (2+1) - dimensional; dispersive long wave equation; Approximate long water wave equation; Wave transformation; The two-variable ( G' /G, 1/G)-expansion; method